The Characterisation of Lactococcus garvieae Isolated in an Outbreak of Septicaemic Disease in Farmed Sea Bass (Dicentrarchus labrax, Linnaues 1758) in Italy - Salogni, Cristian; Bertasio, Cristina; Accini, Adelchi; Gibelli, Lucia Rita; Pigoli, Claudio; Susini, Francesca; Podavini, Eleonora; Scali, Federico; Varisco, Giorgio; Alborali, Giovanni Loris (Pathogens (Basel), 2024)
In aquaculture, Lactococcus garvieae is a common fish pathogen that can cause significant economic losses in several fresh and saltwater species. Despite the extensive range of hosts, L. garvieae infection in sea bass (Dicentrarchus labrax) has rarely been reported. During the summer of 2023, an outbreak occurred in an inland farm in the Gulf of Follonica (Tuscany, Italy). Fish of various sizes were affected, showing apathy, inappetence, erratic swimming and eye lesions, while the mortality was low (2–3% per month). Anatomopathological examinations suggested a septicaemic infection characterised by melanosis, diffuse redness (skin and fins), paleness (gills and internal organs), haemorrhages and splenomegaly. Seventy swabs from the viscera of 14 subjects were collected and colonies similar to Streptococcus spp. grew from all the samples. Lactococcus garvieae was identified via the biochemical tests, API20STREP, MALDI-TOF, 16S rDNA and whole genome sequencing. Genetical characterisation revealed remarkable differences between this isolate and the strains previously isolated in Italian fish farms. Feed treatments with flumequine and erythromycin were ineffective. Considering the limited effects of antimicrobials, preventive measures, such as vaccination and biosecurity, should be implemented.